2023
DOI: 10.3390/cancers15072124
|View full text |Cite
|
Sign up to set email alerts
|

Trajectory of Depression among Prostate Cancer Patients: A Secondary Analysis of a Randomized Controlled Trial

Abstract: Background: While psychological difficulties, such as depression, among prostate cancer patients are known, their longitudinal burden remains understudied. We assessed the burden of depression across low-, intermediate- and high-risk prostate cancer groups, and the association between regret and long-term depression. Methods: Secondary analysis of data from a multi-centered randomized controlled study among localized prostate cancer patients was carried out. Assessments were performed at baseline, and at 3-, 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 55 publications
1
8
0
Order By: Relevance
“…Patients stated that the program filled a gap between the medical care they received in the hospital and their psychosocial survivorship needs that could be traced back to the time of diagnosis, which became more complex post-treatment due to treatment side effects. Indeed, research shows that prostate cancer patients report receiving inadequate information on strategies to address psychosocial needs cooccurring with oncological treatment, such as the need for social support, the adoption of healthier lifestyle habits related to sleep, physical fitness, eating, and stress around treatment and the possibility of cancer reoccurrence [ 32 , 36 , 41 , 42 ]. Patients reported feeling empowered, having greater agency and self-efficacy and confidence that they can better manage their treatment-related side-effects and improve their overall health.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Patients stated that the program filled a gap between the medical care they received in the hospital and their psychosocial survivorship needs that could be traced back to the time of diagnosis, which became more complex post-treatment due to treatment side effects. Indeed, research shows that prostate cancer patients report receiving inadequate information on strategies to address psychosocial needs cooccurring with oncological treatment, such as the need for social support, the adoption of healthier lifestyle habits related to sleep, physical fitness, eating, and stress around treatment and the possibility of cancer reoccurrence [ 32 , 36 , 41 , 42 ]. Patients reported feeling empowered, having greater agency and self-efficacy and confidence that they can better manage their treatment-related side-effects and improve their overall health.…”
Section: Discussionmentioning
confidence: 99%
“…The competency of the program’s lead was also perceived as high, 9.89/10. Together they may have contributed to the PC-PEP intervention’s success and the program’s high rates of compliance whether over the shorter duration of 28 days or the extended period of 6 months [ 32 , 33 ]. Indeed, health recommendations provided to patients by a clinician or health care professional can action positive changes in overcoming unhealthy behaviors especially when patients’ ownership over their own health is emphasized when a sense of partnership in care between clinician and patient is conveyed, when small steps toward the desired changes are identified, and a sense of genuine personal care for patients is communicated [ 73 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, this population has been shown to have higher rates of depression, anxiety, and overall distress symptoms compared to those without a lifetime cancer diagnosis, which are common manifestations of stress [ 6 , 7 , 8 ]. For example, Chhatre and colleagues surveilled 743 patients with PCa over the course of 24 months and found that rates of depression increased significantly from baseline for all cancer-risk groups (14.9% to 43.5% for low-risk group, 24.9% to 43.2% for intermediate-risk, and 21.6% to 47.1% for high-risk) [ 9 ]. Similarly, in another study, 10.9% of PCa patients reported anxiety via the Memorial Anxiety Scale for Prostate Cancer, and 14.1% scored within the anxious range on the Hospital Anxiety and Depression Scale [ 10 ].…”
Section: Introductionmentioning
confidence: 99%